Fiqih Digital: Kajian Etika Penggunaan Artificial Intelligence (AI) dalam Pendidikan Agama Islam - Muhamad Abdilah; Abdul Hamid; Siswanto Siswanto; Ifada Retno Ekaningrum (At-Tadris: Journal of Islamic Education, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed the educational landscape, including Islamic Religious Education. AI offers numerous opportunities to enhance learning effectiveness through personalized instruction, broader access to knowledge, and greater efficiency in educational processes. Nevertheless, the use of AI also raises various ethical concerns, including academic plagiarism, algorithmic bias, technological dependency, the erosion of religious scholarly authority, and threats to data privacy. This study aims to examine the ethical dimensions of AI utilization in Islamic Religious Education from the perspective of digital fiqh. The research employs a qualitative library research approach using content analysis of relevant academic literature. The findings reveal that the use of AI in Islamic education is generally permissible as long as it aligns with Islamic legal principles and contributes to public benefit (maslahah). The framework of maqāṣid al-sharī‘ah serves as the primary foundation for evaluating both the opportunities and risks associated with AI implementation. Ethical principles such as trustworthiness (amanah), verification (tabayyun), public benefit (maslahah), justice (al-'adl), and responsibility (mas'uliyyah) should guide the use of AI within Islamic educational settings. This study concludes that AI should function as a supportive educational tool rather than a replacement for teachers, thereby preserving the fundamental objectives of Islamic education in nurturing faithful, knowledgeable, and morally responsible individuals in the digital era.